Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure, let's solve the quadratic equation [tex]\(x^2 + 4x - 1 = 0\)[/tex] step-by-step by completing the square.
### Step 1: Completing the Square
Given the equation:
[tex]\[x^2 + 4x - 1 = 0\][/tex]
1. First, move the constant term to the other side:
[tex]\[x^2 + 4x = 1\][/tex]
2. To complete the square, we need to add and subtract the square of half the coefficient of [tex]\(x\)[/tex]. The coefficient of [tex]\(x\)[/tex] is 4, so half of it is 2, and squaring it gives us 4. So, we add and subtract 4 inside the equation:
[tex]\[x^2 + 4x + 4 - 4 = 1\][/tex]
3. Write the equation in the form of a perfect square trinomial:
[tex]\[(x + 2)^2 - 4 = 1\][/tex]
4. Now, isolate the perfect square term:
[tex]\[(x + 2)^2 = 5\][/tex]
### Step 2: Solving the Equation
Now we have the equation [tex]\((x + 2)^2 = 5\)[/tex]. To solve for [tex]\(x\)[/tex], take the square root of both sides:
[tex]\[ x + 2 = \pm \sqrt{5} \][/tex]
This gives us two solutions:
[tex]\[ x + 2 = \sqrt{5} \quad \text{or} \quad x + 2 = -\sqrt{5} \][/tex]
Next, solve for [tex]\(x\)[/tex]:
1. For [tex]\( x + 2 = \sqrt{5} \)[/tex]:
[tex]\[ x = \sqrt{5} - 2 \][/tex]
2. For [tex]\( x + 2 = -\sqrt{5} \)[/tex]:
[tex]\[ x = -\sqrt{5} - 2 \][/tex]
So, the solutions are:
[tex]\[ x = -2 + \sqrt{5} \][/tex]
[tex]\[ x = -2 - \sqrt{5} \][/tex]
### Choosing the Correct Answer
Given the options:
- (A) [tex]\( x = 2 \pm 5 \)[/tex]
- (B) [tex]\( x = -2 \pm 5 \)[/tex]
- (C) [tex]\( x = 2 \pm \sqrt{5} \)[/tex]
- (D) [tex]\( x = -2 \pm \sqrt{5} \)[/tex]
The correct answer is:
[tex]\[ \text{(D)} \quad x = -2 \pm \sqrt{5} \][/tex]
So the solutions to the equation [tex]\(x^2 + 4x - 1 = 0\)[/tex] are [tex]\(x = -2 + \sqrt{5}\)[/tex] and [tex]\(x = -2 - \sqrt{5}\)[/tex].
### Step 1: Completing the Square
Given the equation:
[tex]\[x^2 + 4x - 1 = 0\][/tex]
1. First, move the constant term to the other side:
[tex]\[x^2 + 4x = 1\][/tex]
2. To complete the square, we need to add and subtract the square of half the coefficient of [tex]\(x\)[/tex]. The coefficient of [tex]\(x\)[/tex] is 4, so half of it is 2, and squaring it gives us 4. So, we add and subtract 4 inside the equation:
[tex]\[x^2 + 4x + 4 - 4 = 1\][/tex]
3. Write the equation in the form of a perfect square trinomial:
[tex]\[(x + 2)^2 - 4 = 1\][/tex]
4. Now, isolate the perfect square term:
[tex]\[(x + 2)^2 = 5\][/tex]
### Step 2: Solving the Equation
Now we have the equation [tex]\((x + 2)^2 = 5\)[/tex]. To solve for [tex]\(x\)[/tex], take the square root of both sides:
[tex]\[ x + 2 = \pm \sqrt{5} \][/tex]
This gives us two solutions:
[tex]\[ x + 2 = \sqrt{5} \quad \text{or} \quad x + 2 = -\sqrt{5} \][/tex]
Next, solve for [tex]\(x\)[/tex]:
1. For [tex]\( x + 2 = \sqrt{5} \)[/tex]:
[tex]\[ x = \sqrt{5} - 2 \][/tex]
2. For [tex]\( x + 2 = -\sqrt{5} \)[/tex]:
[tex]\[ x = -\sqrt{5} - 2 \][/tex]
So, the solutions are:
[tex]\[ x = -2 + \sqrt{5} \][/tex]
[tex]\[ x = -2 - \sqrt{5} \][/tex]
### Choosing the Correct Answer
Given the options:
- (A) [tex]\( x = 2 \pm 5 \)[/tex]
- (B) [tex]\( x = -2 \pm 5 \)[/tex]
- (C) [tex]\( x = 2 \pm \sqrt{5} \)[/tex]
- (D) [tex]\( x = -2 \pm \sqrt{5} \)[/tex]
The correct answer is:
[tex]\[ \text{(D)} \quad x = -2 \pm \sqrt{5} \][/tex]
So the solutions to the equation [tex]\(x^2 + 4x - 1 = 0\)[/tex] are [tex]\(x = -2 + \sqrt{5}\)[/tex] and [tex]\(x = -2 - \sqrt{5}\)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.